ADVANCE CARE PLANNING FOR MENTAL HEALTH TREATMENT: THE PERSPECTIVES OF AUSTRALIAN MENTAL HEALTH CLINICIANS. Issue 2 (1st June 2013) - Mawren, D; Silvester, W; Newton, R; Fullam, R; Mountjoy, R
Abstract : Background: International research highlights that the successful implementation of Advance Care Planning (ACP) for mental health treatment can depend on clinicians' attitudes and knowledge of Psychiatric Advance Directives (PADs). With proposed revisions to the Victorian Mental Health Act considering the introduction of ACP, it is vital to explore the attitudes and knowledge of mental health clinicians in an Australian setting. Aim: To establish Australian mental health clinicians' knowledge and attitudes regarding PADs. Methods: A national online survey of Australian psychologists and case managers. Results: Of 260 respondents, 67% reported low to very low knowledge of PADs and only 20% reported any experience with PADs. 73% of clinicians welcomed service change that would give consumers more control over their management and 63% would be more inclined to use PADs if the law acknowledged their role as important. PADs were expected to have a positive impact on mental health care (80%) and not pose major limitations to consumer care (65%), however 45% expressed concern that the benefit of PADs may be outweighed by the refusal of indicated treatments such as counselling. Discussion: Australian mental health clinicians have limited exposure to PADs, but display encouraging attitudes towards their potential benefits and related systems changes. Conclusion: Australian mental health clinicians were supportive of the use of PADs and further research will help to develop a sustainable model of ACP for mental health care in Australia.